Working on the Railroad, Walking in Beauty Navajos, Hózhq, and Track Work - Youngdahl, Jay (Utah State University Press, 2011)
"A valuable account of how the Navajo involvement in railroad labor and underlying cultural values interface. It is the sensitivity to that cultural identity that gives the work a special edge and at the same time a broad appeal. It is extremely well written and well organized. Jay Youngdahl tells a good story while applying high standards of scholarship along with an underlying humanism." -Paul Zolbrod, author/translator of Din Bahan: The Navajo Creation Story.
Description based on print version record.
KU Select 2016 Backlist Collection
Keywords: History / Indigenous Peoples of the Americas; History; Electronic books